Performance evaluation of Logistics Listed Enterprises Based on entropy weight TOPSIS - Yao, Yijun; Xiong, Kai (2021 International Conference on E-Commerce and E-Management (ICECEM), 2021)
As an emerging industry in the complex service industry, the objective evaluation of business performance is particularly important for the transformation and upgrading of the logistics industry and the sustainable development of enterprises. This paper selects 12 listed logistics enterprises. Twelve indicators are selected from the five dimensions of profitability, debt paying ability, operation ability, innovation ability and development ability to construct the enterprise operation performance evaluation index system. Entropy method is used to determine the index weight. TOPSIS is used to rank the business performance of enterprises. The results show that the development of logistics enterprises is not balanced. There is still room for improvement of business performance. Based on this, some suggestions are put forward to improve business performance.